Dossier II: Fosas clandestinas en México: Crisis forense y de derechos humanos - Arelí Rojas, Alondra (Quadernos de criminología, 2022)
Clandestine graves have become in a forensic crisis and human rights for 16 years as a consequence of the war on drug. In this article, the purpose is a review of the problem.